1997
DOI: 10.1515/bchm.1997.378.9.1005
|View full text |Cite
|
Sign up to set email alerts
|

Full Length cDNA of Rat RT1.DMa and RT1.DMb and Expression of RT1.DM Genes in Dendritic and Langerhans Cells

Abstract: MHC encoded DM heterodimers and classical MHC class II complexes meet in an endosomal/lysosomal compartment where DM heterodimers support peptide loading of MHC class II. Studies on peptide loading of rat class II and on peptide persistence in cells of the dendritic lineage prompted us to establish full length cDNA clones coding for the subunits alpha and beta of rat DM molecules as well as a mAb directed against the luminal moiety of the beta subunit. Here we describe the establishment of the first full lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The Modo-DMB transcript has a long 3ЈUT of 856 bp. Like the 5ЈUT this region has a low similarity to the placental counterparts, which are generally shorter ( (Kelly et al 1991)], cow [Bota (Niimi et al 1995)], mouse [H2 ], rat [RT1 (Kurth et al 1997)], rabbit [Orcu (Hermal et al 1997)], opossum (Modo), and wallaby (Maru). The consensus sequence derived by simple majority is shown using the single-letter IUPAC code.…”
Section: Dmbmentioning
confidence: 99%
See 1 more Smart Citation
“…The Modo-DMB transcript has a long 3ЈUT of 856 bp. Like the 5ЈUT this region has a low similarity to the placental counterparts, which are generally shorter ( (Kelly et al 1991)], cow [Bota (Niimi et al 1995)], mouse [H2 ], rat [RT1 (Kurth et al 1997)], rabbit [Orcu (Hermal et al 1997)], opossum (Modo), and wallaby (Maru). The consensus sequence derived by simple majority is shown using the single-letter IUPAC code.…”
Section: Dmbmentioning
confidence: 99%
“…The characterization of DM genes in different vertebrate organisms can provide information on the evolution of the Mhc, particularly with regard to the establishment of class II function. To date, gene sequences from placental mammals only, i.e., human, gorilla, chimpanzee, orangutan (Alvarez et al 1998), mouse, rat Kurth et al 1997), cow (Niimi et al 1995), rabbit (Hermal et al 1997), andlemur (O'hUigin andFigueroa 1997), have been reported. In order to gain insights into the evolution of DM and the Mhc, a survey of DM molecules in vertebrates has been initiated.…”
Section: Introductionmentioning
confidence: 99%